Representation of Masin brothers as ``enemies of socialism'' in short stories edited by Nase vojsko publishing house (1966-1987) - Sveda, Josef (Bohemica Olomucensia, 2012)
Short stories about Masin brothers illustrate the way, how the socialistic state regime tried to get a hegemony and to persuade its citizens arguing that people who did not agree with the system were criminals and murderers.